PENINGKATAN PRESTASI SEKOLAH MELALUI KELOMPOK KERJA GURU ( KKG ) SEKOLAH DENGAN MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR - Aminarti Aminarti (LPPM UNISDA, 2020)
Teacher Working Group (KKG) schools and committees / communities can improve learning achievement in SD Negeri Blimbing I Lamongan District. Increasing teachers' understanding of the importance of using the school environment as a source of learning by sensitizing and guiding teachers to understand the importance of utilizing the school environment as a learning resource, developing learning implementation plan (RPP) and learning implementation by utilizing the school environment as a source of learning while keeping the principles -the principle of learning forms that favor learning through relating, experienting, actuating, contextual, transferring.